Pulsed Laser Deposited Zeolite Coatings on Femtosecond Laser-Nanostructured Steel Meshes for Durable Superhydrophilic/Oleophobic Functionalities - Shahbaz Ahmad (Frontiers Media S.A., 2021)
Ultrafast laser structuring has proven to alter the wettability performance of surfaces drastically due to controlled modification of the surface roughness and energy. Surface alteration can be achieved also by coating the surfaces with functional materials with enhanced durability. On this line, robust and tunable surface wettability performance can be achieved by the synergic effects of ultrafast laser structuring and coating. In this work, femtosecond laser-structured stainless steel (SS-100) meshes were used to host the growth of NaAlSi2O6–H2O zeolite films. Contact angle measurements were carried on pristine SS-100 meshes, zeolite-coated SS-100 meshes, laser-structured SS-100 meshes, and zeolite-coated laser-structured SS-100 meshes. Enhanced hydrophilic behavior was observed in the zeolite-coated SS-100 meshes (contact angle 72°) and in laser-structured SS-100 meshes (contact angle 41°). On the other hand, superior durable hydrophilic behavior was observed for the zeolite-coated laser-structured SS-100 meshes (contact angle 14°) over an extended period and reusability. In addition, the zeolite-coated laser-structured SS-100 meshes were subjected to oil–water separation tests and revealed augmented effectuation for oil–water separation.